SULFIDES, SELENIDES, AND TELLURIDES OF PLATINUM AND PALLADIUM: ESTIMATION OF THERMODYNAMIC PROPERTIES - Karzhavin V.K. (My University, 2007)
Investigations in physical chemistry, geochemistry, and other disciplines require the knowledge of the thermodynamic properties of many minerals, chemical compounds, and elements. The plausibility of predictive models obtained in such investigations relies on the accuracy of these data. Unfortunately, necessary thermodynamic data are often absent or show a large scatter in numerous handbooks and research papers. The empirical and semiempirical methods of thermodynamic calculations yield considerable uncertainties. Moreover, it was noted that the experimental methods of the determination of thermodynamic values may also be unreliable. Theoretical studies are impossible without sufficiently accurate thermodynamic data for elements, compounds, and ions. Otherwise, the obtained data may be implausible. The main requirements to thermodynamic values are their reliability, mutual consistency, etc.. In our theoretical study, thermodynamic values are derived by various computational methods using the available reference data and their correlation relationships and functions.